Metal oxide coated and modified platinum-carbon catalyst as well as preparation method and application thereof

By using atomic layer deposition technology on the catalyst support for the proton exchange membrane fuel cell, and downloading platinum at high temperatures, the problem of insufficient corrosion resistance and low activity of the catalyst support is solved, and the stability and activity of the catalyst is significantly improved. , enhances the performance of fuel cells.

CN119400878APending Publication Date: 2025-02-07JIANGHAN UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411556303.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing proton exchange membrane fuel cell catalyst support has insufficient corrosion resistance and low catalyst activity, resulting in a decrease in fuel cell performance and shortened working life.

Method used

Atomic layer deposition technology is used to coat titanium oxide on the surface of the carbon support to form a titanium oxide modified carbon support. Then, platinum carbon catalyst with improved activity and stability is prepared with improved titanium oxide modified carbon support.

Benefits of technology

It significantly improves the electrochemical corrosion resistance and stability of the catalyst support, improves the activity and durability of the catalyst, and enhances the performance of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400878A_ABST
    Figure CN119400878A_ABST
Patent Text Reader

Abstract

The invention relates to a metal oxide coated and modified platinum-carbon catalyst and a preparation method and application thereof, and the coating and modification method of the carbon material comprises the following steps: coating the surface of the carbon material with a metal oxide through an atomic layer deposition method, and then carrying out platinum loading on the coating structure to obtain the carbon-platinum catalyst coated with a metal oxide modification layer. Due to modification of the metal oxide, contact between the carbon carrier and an electrolyte is blocked, and electrochemical corrosion of the carbon carrier in an electrochemical operation process is prevented, so that the stability of the carbon carrier is enhanced, and the overall stability of the platinum-carbon catalyst is improved; in addition, because the platinum nanoparticles have good dispersibility on a titanium oxide interface and other factors, the electrochemical specific surface area of the catalyst is also increased to a certain extent, and thus excellent electrocatalytic activity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-efficiency carrier-modified cathode oxygen reduction catalyst-a titanium oxide-modified carbon carrier-supported platinum catalyst, and belongs to the technical field of new energy materials. Background Art

[0002] As a highly efficient energy conversion device, proton exchange membrane fuel cell (PEMFC) can directly convert chemical energy into electrical energy without being restricted by the Carnot cycle. It has the advantages of high efficiency, wide fuel sources, and environmental friendliness, and is considered to be one of the most promising energy conversion technologies. Currently, the most active and widely used catalyst for proton exchange membrane fuel cells is Pt / C catalyst.

[0003] Platinum metal is expensive and its resources are limited. In order to improve its utilization rate and reduce its dosage, platinum is highly dispersed in the form of nano-particles on carbon carriers. Due to the high specific surface energy of the catalyst, the electronic structure of the catalyst and the carrier is quite different. They only rely on weak interactions to adhere to each other. Platinum nanoparticles can easily migrate and grow on the surface of the carrier, resulting in a decrease in the surface area of ​​the catalyst and a decrease in activity, which in turn leads to a gradual decline in the performance of the fuel cell during actual use, a shortened working life, and a decrease in reliability. Nanocarbon black is widely used in the field of catalyst carriers due to its large specific surface area, nano-particle size, good thermal conductivity, electrical conductivity and adsorption properties. However, under the working conditions of fuel cells (cathode pH <1, high potential 0.6-1.2V, oxygen-rich environment, and high temperature conditions (50-90°C), the carbon carrier is prone to electrochemical corrosion. The corrosion of the carbon carrier will cause the separation of the platinum particles from the carrier, causing the platinum particles to fall off and reduce the durability of the catalyst.

[0004] The existing patent CN118712404A discloses a method for preparing a Pt / TiO2-C catalyst. The corrosion resistance of the catalyst carrier is not ideal. Meanwhile, the patent CN114976078B proposes a platinum-carbon catalyst for a proton exchange membrane fuel cell and a method for preparing the same. The electrochemical active area of ​​the electrocatalyst in Example 1 of the technology reaches 68.95 m 2 ·g -1 , also needs to be improved. Summary of the invention

[0005] Based on the above problems, the purpose of the present invention is to provide a modified carbon material with excellent properties and a preparation method thereof, so as to solve the problems of insufficient corrosion resistance of existing catalyst carriers and low catalyst activity. The method firstly uses atomic layer deposition technology to accurately and uniformly coat titanium oxide on the surface of a carbon carrier to obtain a titanium oxide-modified carbon black carrier with enhanced electrochemical corrosion resistance, and then uses a colloid method to load platinum at high temperature, and after washing, drying and grinding, obtains a platinum-carbon catalyst on a titanium oxide-modified carbon carrier with improved activity and stability.

[0006] To achieve the above purpose, the technical solution provided by the present invention is:

[0007] The preparation method of titanium oxide modified platinum carbon catalyst comprises the following steps:

[0008] Step 1, grinding the nano carbon black particles evenly for standby use;

[0009] Step 2: coating a metal oxide film on the surface of the nano carbon black particles by atomic layer deposition to obtain a carbon carrier modified with a metal oxide coating layer, i.e., a modified carbon carrier;

[0010] Step 3, dispersing the modified carbon support in step 2 evenly in a solvent, adding a platinum source precursor solution, and adding an alcohol solution at the same time to obtain a mixed solution;

[0011] Step 4: adjust the pH of the mixed solution in step 3 to 7-13, heat to 80-180° C. and keep warm for reaction, and obtain a metal oxide-coated carbon platinum catalyst after washing, drying and grinding.

[0012] In the above method, in step 1, the nano carbon black is carbon black from Cabot Corporation, or other carbon black.

[0013] In the above method, in step 1, grinding includes using an agate mortar, or other mortars, to make the agglomerated carbon black particles more evenly distributed.

[0014] In the above method, in step 2, the carbon black particles are treated with ozone to increase the defect sites and the content of oxygen-containing groups on the surface of the carbon black, which is beneficial to the subsequent titanium oxide deposition.

[0015] In the above method, in step 2, the precursors in the atomic layer deposition coated titanium oxide are titanium tetraisopropoxide (TTIP) and water or titanium tetraisopropoxide and titanium tetrachloride, the temperature of the titanium precursor is set to 40-80°C, the temperature of the water is set to 20-80°C, and the temperature of the reaction chamber is set to 180-250°C.

[0016] In the above method, in step 2, the atomic layer deposition of titanium oxide is achieved by repeating the following process: 1) 0.2S precursor pulse, accompanied by N2 purge, the precursor is blown into the reaction chamber, repeated three times. 2) 30S N2 purge, cleaning. 3) 0.2S water purge, accompanied by N2 purge, the precursor is blown into the reaction chamber, repeated three times. 4) 30S N2 purge, cleaning. Repeat the process of 1)-4) to complete the coating of the atomic layer deposition of titanium oxide to obtain a titanium oxide modified carbon support material.

[0017] In the above method, in step 2, titanium oxide is coated on the surface of the carbon carrier through an atomic layer deposition process, which is beneficial to separate the contact between the carbon carrier and the electrolyte, improve the corrosion resistance of the carbon carrier, and provide higher stability for the catalyst carrier.

[0018] In the above method, the solvent in step 3 is a mixture of water and ethanol, methanol, ethylene glycol, isopropanol in any proportion or a pure solution.

[0019] In the above method, the platinum source precursor solution in step 3 is an aqueous solution of chloroplatinic acid or its salt, chloroplatinous acid or its salt, hexahydroxyplatinic acid or its salt, platinum nitrate, platinum sulfate, ammonium platinate, tetraamineplatinum oxalate, and tetraamineplatinum malonate, and the solvent is a mixed solution or a pure solution of water and ethanol, methanol, ethylene glycol, and isopropanol in any proportion.

[0020] In the above method, the alcohol solution in step 3 is a mixture of ethylene glycol, ethanol, propanol, glycerol in any proportion or a pure solution, or an alcohol-water solution with a water content of less than 80 v / v%.

[0021] In the above method, in step 2, titanium oxide modifies the carbon support with platinum catalyst, and titanium oxide is evenly coated on the surface of the carbon support, blocking the direct contact between the electrolyte and the carbon support, increasing the electrochemical corrosion resistance of the carbon support, and improving the stability of the support. Titanium oxide has a strong affinity with platinum particles, which is stronger than the interaction between platinum and carbon black, so that the activity and stability of the titanium oxide-modified carbon support with platinum catalyst are significantly improved.

[0022] In the present invention, the titanium oxide modified carbon carrier supported platinum catalyst is used as a cathode catalyst of the membrane electrode of a proton exchange membrane fuel cell, which can effectively improve the performance of the fuel cell.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] 1. The carbon carrier is modified by atomic layer deposition of titanium oxide, and titanium oxide is precisely deposited on the surface of the carbon carrier. Compared with the traditional impregnation method, the atomic layer deposition technology can construct a uniform and dense sub-nanometer titanium oxide coating layer, which solves the problem that the impregnation method cannot uniformly construct a uniform and dense ultra-thin titanium oxide layer, and significantly improves the corrosion resistance of the catalyst carrier.

[0025] 2. In the titanium oxide modified carbon carrier platinum catalyst, on the one hand, after being coated with titanium oxide, the exposure and contact of the carbon carrier in the electrolyte are reduced, its corrosion in the electrochemical process is inhibited, the carbon carrier is protected, and the carrier structure is more stable, thereby improving the overall stability of the catalyst. On the other hand, there is an interaction between the electron cloud structure of titanium oxide and platinum particles, which has a stronger adsorption force than platinum and carbon, reducing the shedding, dissolution and aggregation of platinum particles, significantly improving the utilization rate of platinum particles, and at the same time improving the durability of the catalyst.

[0026] 3. The preparation process of the titanium oxide-modified carbon-supported platinum catalyst is simple, efficient and universal, and easy to prepare on a large scale. The activity and stability of oxygen reduction have been greatly improved, and its cathode catalytic performance in proton exchange membrane fuel cells has also been greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a transmission electron microscope (TEM) image of the titanium oxide modified carbon support prepared in Example 1 of the present invention;

[0028] Figure 2 This is a high-resolution transmission electron microscopy (HRTEM) image of the titanium oxide-modified carbon support prepared in Example 1 of the present invention;

[0029] Figure 3 This is a high-resolution transmission electron microscopy (HRTEM) image of the unmodified nanocarbon black used in Example 1 of the present invention;

[0030] Figure 4 This is a high-resolution transmission electron microscopy (HRTEM) image of the titanium oxide-modified carbon carrier platinum-loaded material obtained in Example 2 of the present invention;

[0031] Figure 5 Cyclic voltammetry test graphs of the titanium oxide modified carbon support material (C@5TiO2) prepared in Example 1 of the present invention, the support of Comparative Example 1, Comparative Example 2, and the support of Comparative Example 3;

[0032] Figure 6 The cyclic voltammetry test diagram of the titanium oxide modified carbon carrier platinum-loaded material (C@5TiO2-Pt) prepared in Example 2 and the carbon carrier platinum-loaded materials prepared in Comparative Examples 1, 2 and 3 in Example 4 of the present invention;

[0033] Figure 7 This is a graph showing the oxygen reduction performance of the titanium oxide modified carbon carrier platinum-loaded material (C@5TiO2-Pt) prepared in Example 2 and commercial platinum carbon (Pt / C) in Example 5 of the present invention. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is described below by specific embodiments in conjunction with the accompanying drawings. It should be understood that the one or more steps mentioned in the present invention do not exclude the presence of other method steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and is not intended to limit the order of arrangement of each method or to define the scope of implementation of the present invention. Changes or adjustments in their relative relationships can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.

[0035] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0036] The nano carbon black powder in the following examples is Ketjen black, and its nitrogen adsorption specific surface area is 800m 2 / g, with a diameter of 30 to 50 nm.

[0037] Example 1

[0038] Weigh an appropriate amount of nano carbon black particles and place them in an agate mortar, grind until the powder is uniform and no obvious particles can be seen by the naked eye. Weigh the ground nano carbon black powder and put it in a jar in the reaction chamber, place the jar in the atomic layer deposition equipment, set the program, and start the coating of the titanium oxide material after ozone treatment. This process uses titanium tetraisopropoxide and water as precursors of titanium and oxygen, respectively. The pulse pressure of the titanium precursor and water is set to 7torr, the temperature of the titanium precursor is set to 64°C, the temperature of the water precursor is set to 30°C, and the temperature of the reaction chamber is set to 250°C.

[0039] The TiO2 ALD coating on the surface of the nanocarbon black particles is achieved by repeating the following process: 1) 0.2S titanium precursor pulse, accompanied by N2 purge, blowing the titanium precursor into the reaction chamber, repeat three times. 2) 30S N2 purge, cleaning. 3) 0.2S oxygen precursor pulse purge, accompanied by N2 purge, blowing the oxygen precursor into the reaction chamber, repeat three times. 4) 30S N2 purge, cleaning. Repeat the process 1)-4) to complete the ALD coating. Repeat the above process 5 times to obtain a coating layer with a coating thickness of 0.3-0.5nm, and the obtained carrier material is recorded as C@5TiO2.

[0040] The TEM results of this sample are as follows Figure 1 As shown, a single particle of nanocarbon black presents a spherical structure with a particle size of about 30 nm, and multiple particles adsorb each other to form typical agglomerates.

[0041] The HRTEM results of this sample are as follows Figure 2 As shown, it can be seen that the surface of the coated carbon black material forms a contrast of uneven modifications within about 0.3 to 0.5 nm, compared with the uncoated nanocarbon black single particle ( Figure 3 ), it can be judged that the titanium oxide material obtained in this embodiment is modified by atomic layer deposition.

[0042] Example 2

[0043] Step 1: Take 120 mg of the titanium oxide-coated nanocarbon black material in Example 1 into a 250 ml beaker, add 60 ml of deionized water and 60 ml of ethanol, and stir ultrasonically for 1 hour to fully disperse the material. Add 100 ml of ethylene glycol and 20 ml of chloroplatinic acid with a platinum concentration of 1.5 mg / ml into a three-necked flask, stir magnetically for 5 minutes to mix well, and then pour the above mixed solution.

[0044] Step 2: by adding 1 mol L -1 The pH of the mixed solution was adjusted to 8-10 with a NaOH solution. The temperature was then raised to 130°C and maintained for 3 hours, followed by natural cooling. The pH of the cooled catalyst solution was adjusted to 3-5, and then washed to neutrality by a vacuum pump filtration device, collected and dried at 80°C in vacuum for 8 hours to obtain a titanium oxide-modified carbon support platinum catalyst material C@5TiO2-Pt.

[0045] The HRTEM image of the sample (such as Figure 4 ) shows the uniform distribution of platinum nanoparticles on the surface of titanium oxide modified carbon support, with a lattice spacing of 0.224 nm matching the Pt (111) plane, corresponding to the face-centered cubic (fcc) structure of Pt crystals.

[0046] Comparative Example 1

[0047] A method for preparing a Pt / TiO2-C catalyst comprises the following steps:

[0048] Step 1, dissolving 5g of tetrabutyl titanate and 3g of Ketjen black in 150ml of ultrapure water and stirring to obtain a mixed solution, then slowly dropping a Na2CO3 solution into the mixed solution and stirring and reacting at 80°C until the mixed solution is completely evaporated to dryness, collecting the evaporated materials, washing them with ultrapure water, and then drying them to obtain a composite carrier precursor, the drying temperature is 80°C, and the drying time is 12h; the Na2CO3 solution is a mixture of 2g of Na2CO3 and 125ml of ultrapure water;

[0049] Step 2: Load the composite carrier precursor into the reaction container in the reactor, and calcine the composite carrier precursor in a nitrogen protective atmosphere to obtain a TiO2-C composite carrier. The calcination is specifically as follows: control the temperature in the reactor to rise to 440°C at a rate of 2°C / min, and keep warm for 1 hour;

[0050] Step 3, 1g of the TiO2-C composite carrier is mixed with 80ml of ethylene glycol solution and stirred to obtain a slurry, and then 21.3ml of 100g / L potassium tetrachloroplatinate ethylene glycol solution is gradually added to the slurry under stirring. After the step of adding the potassium tetrachloroplatinate ethylene glycol solution to the slurry is completed, 1g of sodium hydroxide and 1.7g of sodium citrate are added to the slurry to adjust the pH, and finally the stirred slurry is placed in an oven at 150°C for reaction for 1.5h to obtain a mixed slurry;

[0051] Step 4: The mixed slurry is filtered and washed with ultrapure water for multiple times, and finally dried at 80° C. for 12 h to obtain a Pt / TiO2-C catalyst.

[0052] Weigh 10 mg of the Pt / TiO2-C catalyst prepared in Example 1, add 3.8 ml of ultrapure water and 1.2 ml of isopropanol to prepare catalyst ink, and use a pipette to transfer 7 μl of ink droplets to a surface area of ​​0.19625 cm 2 The catalyst support durability test was carried out on the platinum carbon electrode surface.

[0053] Comparative Example 2

[0054] Referring to the preparation method of Example 2, the titanium oxide-coated nano-carbon black material in step 1 is replaced with a nano-carbon black material, and the other steps remain unchanged, to obtain a pure carbon black-supported platinum material C-Pt.

[0055] Comparative Example 3

[0056] This example refers to the preparation method of Example 1 to prepare C@10TiO2. The difference from Example 1 is that after step (4), the process of 1) to 4) is repeated to complete the ALD coating. The above process is repeated 10 times to make the thickness of the TiO2 coating layer 0.6-1.0nm.

[0057] Then, the C@10TiO2-Pt catalyst was prepared according to steps 1 and 2 of Example 2.

[0058] Example 3

[0059] Cyclic voltammetry tests were performed on the titanium oxide modified carbon black platinum-loaded material C@5TiO2-Pt prepared in the above Example 2, the Pt / TiO2-C catalyst of Comparative Example 1, the pure carbon black platinum-loaded material C-Pt prepared in Comparative Example 2, and the titanium oxide modified carbon black platinum-loaded material C@10TiO2-Pt prepared in Comparative Example 3.

[0060] In the test results, Figure 5 As shown, after a titanium oxide coating layer is deposited on the surface of a carbon black carrier by atomic layer deposition (Example 2), there is no difference in the position of the oxidation peak near 0.4V (V vs. RHE) of the carrier curve, while the carbon carrier without titanium oxide modification (Comparative Example 2) has a very obvious oxidation peak, indicating that the carbon carrier has obvious carbon oxidation, that is, the carbon carrier has been corroded, and the carbon carrier modified with titanium oxide has almost no peak at the same position, indicating that the oxidation state modification has a significant protective effect on the carbon carrier. The carrier cyclic voltammetry curve of the Pt / TiO2-C catalyst prepared in Comparative Example 1 has a slightly obvious oxidation peak at the same position, and the current of the double-layer capacitor of the material in Comparative Example 1 is significantly greater than that of the titanium oxide modified carbon material prepared in Example 2, indicating that the carbon carrier in Comparative Example 1 has a certain corrosion, and when the number of ALD coated TiO2 circles is too much, it will also affect the performance of the modified carbon carrier, as shown in the curve of Comparative Example 3. This may be due to the long time of high-temperature reaction in the ALD reaction chamber, which makes more titanium oxide agglomerate into island distribution.

[0061] Example 4

[0062] Weigh 30 mg of the titanium oxide modified carbon support platinum (C@5TiO2-Pt) catalyst prepared in Example 2 and the titanium oxide modified carbon support platinum (C@10TiO2-Pt) catalyst prepared in Comparative Example 3 respectively and put them into a small glass bottle, add 7.5 mL of deionized water, and disperse them evenly by ultrasonication for 30 minutes. Then, take 1 mL of the above dispersion and add it into a small centrifuge tube, add 1 ml of isopropanol and 100 μL of Nafion solution, and use an ultrasonic cleaner to ultrasonicate for 15 minutes to form a uniformly dispersed ink-like solution. Then, use a pipette to take 10 μL of the prepared slurry, and evenly drip it onto the working electrode in small amounts and multiple times, and let it dry naturally at room temperature.

[0063] The ink prepared from the above electrode materials was subjected to electrochemical cyclic voltammetry test. The test process adopted the traditional three-electrode system and was carried out on a CHI750E electrochemical workstation. The prepared glassy carbon electrode coated with catalyst was used as the working electrode, the saturated calomel electrode (SCE) was used as the reference electrode, and platinum was used as the counter electrode. The electrolyte was 0.1 mol L -1 HClO4 solution, and all tests were carried out at room temperature.

[0064] The test potential range is -0.3~1.1V, first at 100mV s -1 The catalyst was activated and surface cleaned by scanning at a scan rate of 50 mV s for 20 cycles. -1 The initial CV curve was obtained by scanning for 3 cycles at a scan rate of 1.5 Å.

[0065] like Figure 6 As shown in the figure, under the same test, the titanium oxide modified carbon supported platinum catalyst (C@5TiO2-Pt) of Example 2 has a higher electrochemical hydrogen evolution area than the catalyst (C@10TiO2-Pt) of Comparative Example 3. That is, the size of the active area of ​​the electrode surface participating in the electrochemical reaction. According to the hydrogen adsorption peak, the ECSA of the titanium oxide modified carbon supported platinum catalyst (C@5TiO2-Pt) prepared in Example 2 is calculated to be 97.57 m 2 g -1 The ECSA of the Pt / TiO2-C catalyst prepared in Comparative Example 1 is 57.53 m 2 g -1 The ECSA of the pure carbon black platinum-loaded material C-Pt prepared in Comparative Example 2 is 70.02 m 2 g -1 , while the ECSA of the catalyst (C@10TiO2-Pt) prepared in Comparative Example 3 is 54.59m 2 g -1 .

[0066] Example 5

[0067] The catalytic oxygen reduction reaction of the titanium oxide modified carbon-supported platinum material (C@5TiO2-Pt) of Example 2 and commercial platinum carbon (Pt / C) was scanned under oxygen saturation, and the electrolyte was 0.1 mol L -1 The test was carried out at room temperature. Figure 7 It can be seen that the C@5TiO2-Pt material has a higher half-wave potential.

[0068] The above shows and describes the basic method, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a metal oxide coated platinum-carbon catalyst, characterized in that: The following steps are involved: Step 1, grinding the nano carbon black particles evenly for standby use; Step 2: coating a metal oxide film on the surface of the nano carbon black particles by atomic layer deposition to obtain a carbon carrier modified with a metal oxide coating layer, i.e., a modified carbon carrier; Step 3, dispersing the modified carbon support in step 2 evenly in a solvent, adding a platinum source precursor solution, and adding an alcohol solution at the same time to obtain a mixed solution; Step 4: adjust the pH of the mixed solution in step 3 to 7-13, heat to 80-180° C. and keep warm for reaction, and obtain a metal oxide-coated carbon platinum catalyst after washing, drying and grinding.

2. The method for preparing a metal oxide coated carbon platinum catalyst according to claim 1, characterized in that: In the step 1, the nano carbon black is one of Ketjen black, Cabot black, carbon nanotubes, and acetylene black, and the particle size of the nano carbon black is 10 to 100 nm.

3. The method for preparing a metal oxide coated carbon platinum catalyst according to claim 1, characterized in that: In step 2, the metal oxide includes one of titanium oxide, tin oxide, zirconium oxide and cerium oxide.

4. The method for preparing a metal oxide coated carbon platinum catalyst according to claim 3, characterized in that: The specific steps of step 2 include: loading nano carbon black particles into a tank of an atomic layer deposition device, using titanium tetraisopropoxide and water as titanium and oxygen precursors respectively, setting the temperature of the reaction chamber to 180-250° C., setting the pulse pressures of the titanium precursor and water to 4-15 torr, setting the temperature of the titanium precursor to 40-80° C., setting the temperature of the water precursor to 20-80° C., and using ozone to pretreat the nano carbon black particles before atomic layer deposition.

5. The method for preparing a metal oxide coated carbon platinum catalyst according to claim 1, characterized in that: In step 2, the coating layer thickness is controlled to be less than 1 nm.

6. The method for preparing a metal oxide coated carbon platinum catalyst according to claim 1, characterized in that: The solvent in step 3 is a mixture of water and ethanol, methanol, ethylene glycol, isopropanol in any proportion or a pure solution.

7. The method for preparing a metal oxide coated carbon platinum catalyst according to claim 1, characterized in that: In step 3, the platinum source precursor solution is an aqueous solution of chloroplatinic acid or its salt, chloroplatinous acid or its salt, hexahydroxyplatinic acid or its salt, platinum nitrate, platinum sulfate, ammonium platinate, tetraamineplatinum oxalate, and tetraamineplatinum malonate, and its solvent is a mixed solution or a pure solution of water and ethanol, methanol, ethylene glycol, and isopropanol in any proportion.

8. The method for preparing a metal oxide coated carbon platinum catalyst according to claim 1, characterized in that: The alcohol solution in step 3 is a mixture of ethylene glycol, ethanol, propanol, glycerol in any proportion or a pure solution, or an alcohol-water solution with a water content of less than 80 v / v%.

9. A metal oxide coated and modified carbon platinum catalyst obtained by the preparation method according to any one of claims 1 to 8.

10. The metal oxide coated and modified carbon platinum catalyst according to claim 9 is used as a cathode catalyst of a membrane electrode of a proton exchange membrane fuel cell.